Availability of type II diabetic families for detection of diabetes susceptibility genes. - Cook, J; Page, R; O'Rahilly, S; Levy, J; Holman, R; Barrow, B; Hattersley, A; Shaw, A; Wainscoat, J; Turner, R (1993)
Type II diabetes is a familial disorder, as evidenced by the increased prevalence in monozygotic cotwins and first-degree relatives of affected subjects; however, its genetic etiology is largely unknown. Well-characterized pedigrees are an essential resource for the study of susceptibility genes for type II diabetes. This study describes a 5-yr search for type II diabetic families in Oxfordshire, U.K. We interviewed 950 type II diabetic subjects concerning the availability of first-degree relatives; 127 Caucasian families ascertained through a proband with type II diabetes were studied, and 589 first-degree relatives were characterized. Three large pedigrees with maturity-onset diabetes of the young, and 8 multiplex multigenerational type II diabetic pedigrees were identified. We identified 12 sib-pairs in which both siblings had type II diabetes; however, only 7 sib-pairs had both parents alive, and 2 of these had both parents affected. If one also considers one sib having diabetes and one sib having glucose intolerance as being an affected sib-pair, we identified 30 sib-pairs of which 7 had both parents affected and probably had bilineal inheritance. We identified 76 complete nuclear families with both parents and offspring available for study, but only 6 were of optimal structure for linkage analysis. In conclusion, multiplex pedigrees and type II diabetic sib-pairs with living parents are uncommon, and their ascertainment requires a substantial investment of resources. Large-scale collaborative multicenter initiatives would be needed to collect a large resource of family material for the study of susceptibility genes for type II diabetes.